Experimental investigation on performance enhancement of forced draft wet cooling towers with special emphasis on the role of stage numbers. (15th October 2016) - Rahmati, Mehdi; Alavi, Seyed Rashid; Tavakoli, Mohammad Reza
Graphical abstract: Highlights: Effects of several input parameters on the cooling tower performance are studied. The temperature distribution is visualized by the use of captured thermal images. The general trend of temperature histograms is similar to the Gaussian distribution. Regression analysis is utilized in order to develop general mathematical equations. Some practical procedures are suggested so as to reach optimum performance. Abstract: Wet cooling towers play a prominent role in the transfer of waste heat from industrial thermodynamic cycles. However it is a complicated task to dictate and optimize their operational conditions on account of different mass and heat transfer mechanisms between water and air flows. In this research, air mass flow rate, hot water temperature, water flow rate and stage numbers of packing are changed experimentally in order to investigate their influences on the cooling tower performance. As a matter of fact, this research attempts to focus on packing density effects with an emphasis on the role of stage numbers of packing. Consequently, the obtained results indicate that coefficient of efficiency is in direct relation with the hot water temperature, stage numbers of packing and air mass flow rate, while it diminishes by increasing the water flow rate. On the other hand, the captured thermal images and pertinent temperature histograms are investigated so as to visualize and calculate the temperature distribution within the studied cooling tower. Eventually, mathematical equations are derived from regression analysis of the measured data to recommend some practical procedures for the sake of reaching optimum operating conditions of forced draft wet cooling towers.